Neuroticism trait personality and social media fatigue in early adults - Nurhamidin, Jeskhia; Huwae, Arthur (International Journal of Public Health Science (IJPHS), 2024)
Social media is a means of digital-based self-exploration, and the formation of personality traits such as neuroticism. Excessive use of social media, based on a strong neuroticism trait, can cause individuals to experience social media fatigue. This study aims to determine the relationship between neuroticism trait personality and social media fatigue in early adulthood. The method used is a quantitative correlational design. The number of participants involved was 136 early adults using social media, obtained using an accidental sampling technique. The scale used in this research is big five inventory (α=.890) to measure neuroticism trait personality and the social media fatigue scale (α=.934) to measure social media fatigue. The data analysis method uses the product moment correlation test from Karl Pearson. The results showed that there was a significant positive relationship between neuroticism trait personality and social media fatigue in early adulthood (r=.361 and sig.=.000). This indicates that the neuroticism personality trait is a factor that can cause social media fatigue in early adulthood. Training and forming a healthy personality by maintaining emotional stability can help the process of self-exploration in social media so that they can complete developmental tasks properly as early adults.